Coffee Wilt Disease 2010
DOI: 10.1079/9781845936419.0028
|View full text |Cite
|
Sign up to set email alerts
|

Coffee wilt disease in Uganda.

Abstract: This chapter describes the current status of coffee wilt disease (CWD, Gibberella xylarioides) in Uganda, including its occurrence and distribution, its impact on coffee production, the factors affecting its severity and incidence, and country-specific practices for its control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The disease kills coffee bushes so that, very soon after its detection on-farm, farmers will experience complete loss of income from coffee. Yields decline rapidly; a 77% loss in yield of robusta coffee at the national level in Uganda was reported by Hakiza et al (2009). Drastic yield reductions and hence income reductions, force smallholder coffee farmers to diversify further or even leave agriculture altogether, sometimes after generations of coffee cultivation.…”
Section: Coffee Wilt Disease (Cwd)mentioning
confidence: 96%
See 1 more Smart Citation
“…The disease kills coffee bushes so that, very soon after its detection on-farm, farmers will experience complete loss of income from coffee. Yields decline rapidly; a 77% loss in yield of robusta coffee at the national level in Uganda was reported by Hakiza et al (2009). Drastic yield reductions and hence income reductions, force smallholder coffee farmers to diversify further or even leave agriculture altogether, sometimes after generations of coffee cultivation.…”
Section: Coffee Wilt Disease (Cwd)mentioning
confidence: 96%
“…One agriculturist reported that he had observed the disease first in the 1970s on a large abandoned plantation on the road to Aketi, which confirmed other reports that the disease had re-emerged as a serious problem in this part of Africa at that time-just when most scientific authorities considered it as a minor problem (Flood 1996). Surveys were also undertaken in adjacent Uganda in the mid 1990s and these confirmed the presence of the pathogen there (Hakiza et al 2009). …”
Section: Coffee Wilt Disease (Cwd)mentioning
confidence: 97%
“…Another example of re-emergence is Coffee Wilt Disease (CWD) in Africa which is causing significant yield losses e.g. 77 % loss of robusta yields in Uganda (Hakiza et al 2009). CWD is of particular significance because unlike many other coffee pests, it kills the trees and the farmer, who is often unable to replace his crop easily, faces major income shortfalls.…”
Section: Case Study 2 -Coffee Wilt Disease In Africamentioning
confidence: 99%
“…F. xylarioides causes a lethal vascular wilt of coffee due to the obstruction of the xylem vessels and the disruption of water supply to the aerial organs (45,56,107). Infection leads to the death of the tree within a period that varies from a few weeks to six months (53,106,107).…”
Section: Main Diseases and Pests Of Arabica Coffeementioning
confidence: 99%